A method for rapidly preparing a SiO2 coating on a C / C composite material surface

By depositing an energetic thin film on the surface of C/C composite material and utilizing the energy storage effect of ZrO2 nanoparticles, the problems of density and process efficiency of SiO2 coating on the surface of C/C composite material were solved, realizing rapid and efficient SiO2 coating preparation and avoiding thermal damage to the substrate.

CN120818785BActive Publication Date: 2025-12-23NINGBO INST OF NORTHWESTERN POLYTECHNICAL UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511278456.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-09
Publication Date
2025-12-23
Estimated Expiration
2045-09-09

AI Technical Summary

Technical Problem

Existing methods for preparing SiO2 coatings on C/C composite surfaces suffer from poor coating density, low process efficiency, and thermal damage to the substrate, making synergistic optimization difficult.

Method used

Energetic thin film technology is used to deposit an energetic thin film on the surface of C/C composite material. The exothermic reaction promotes the pyrolysis and reaction of SiO2 precursor. Combined with the energy storage effect of ZrO2 nanoparticles, the rapid deposition and density of SiO2 coating are achieved.

Benefits of technology

Rapid and efficient preparation of SiO2 coatings was achieved, with a coating density of 98.5%, reduced thermal damage to the substrate, and a process cycle shortened to less than 9 hours.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120818785B_ABST
    Figure CN120818785B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of composite material coating preparation, and discloses a method for rapidly preparing a SiO2 coating on the surface of C / C composite material, which comprises the following steps: step S1, carrying out base pretreatment on the C / C composite material to improve the surface wettability; step S2, depositing an energy-containing film on the surface of the product obtained in step S1; step S3, coating SiO2 precursors on the surface of the product obtained in step S2, coating ZrO2 nanoparticles on the SiO2 precursors, igniting the energy-containing film, and obtaining the SiO2 coating. The coating preparation method is economical and efficient, the obtained coating has a density of 98.5%, and the base thermal damage problem of the composite material is effectively avoided.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of composite coating preparation, in particular to a method for rapidly preparing a SiO2 coating on the surface of a C / C composite material. BACKGROUND

[0002] C / C composite materials reinforced by carbon fibers have irreplaceability in extreme environment fields such as aerospace thermal protection, rocket engine nozzles, and brake systems due to their high specific strength, excellent high-temperature resistance (>2000℃), and low thermal expansion coefficient. The lightweight characteristics (density <2.0 g / cm 3 ) of the material can significantly improve the load efficiency of aircraft. However, in an oxidizing environment (>450℃), the reaction of the carbon matrix with oxygen generates CO / CO2 gas, leading to mass loss and structural failure, which is a core bottleneck restricting its long-term service. To address this, the commonly used method is to coat an inert SiO2 coating on the surface of the C / C composite material.

[0003] The existing preparation of SiO2 coating on the surface of C / C composite material is mostly by chemical vapor deposition (CVD) or sol-gel method, which has the problems of long process cycle (such as CVD requiring 10-30 hours), insufficient coating adhesion (porosity >5%), and difficulty in withstanding thermal shock load. The B2O3@SiO2 coating prepared by multi-layer embedding combined with hot dipping in the patent with publication number CN114644531B solves the problem of insufficient coating adhesion, but requires multiple high-temperature treatments and has high energy consumption. The gradient design of SiC transition layer + refractory metal carbide intermediate layer + La2Hf2O7 outer coating in the patent with application number CN202410934685.0 improves the ablation resistance of the material, but requires multiple high-temperature treatments (>1600℃), has complicated process steps, and is prone to causing substrate damage. The coating prepared by plasma spraying in the patent with application number CN202410901430.4 can shorten the cycle, but it is difficult to control the uniformity of the coating on complex curved surfaces, and the equipment investment cost is too high. The use of MoSi2 siliconizing combined with SiO2 adsorption in the patent with application number CN202411448281.7 improves the oxidation resistance, but the siliconizing process easily causes the substrate to become brittle, and the adsorption layer is prone to peeling under dynamic thermal stress.

[0004] The current technology generally has the problems of poor coating density, low process efficiency, and thermal damage to the substrate. Therefore, it is urgent to develop a method for preparing a SiO2 coating on the surface of a C / C composite material that has rapid forming, strong interface bonding, and low thermal shock. SUMMARY

[0005] The technical problem solved by the present application is that the preparation method of the existing SiO2 coating on the surface of C / C composite material is difficult to optimize the three aspects of coating density, process efficiency and substrate heat damage, and to overcome the defects of the prior art, the present application provides a method for rapidly preparing SiO2 coating on the surface of C / C composite material.

[0006] The present application provides a method for rapidly preparing SiO2 coating on the surface of C / C composite material, comprising the following steps:

[0007] Step S1, the substrate of C / C composite material is pretreated to improve the surface wettability;

[0008] Step S2, depositing an energy-containing film on the surface of the product obtained in step S1;

[0009] Step S3, coating SiO2 precursor on the surface of the product obtained in step S2, coating ZrO2 nanoparticles on the SiO2 precursor, then igniting the energy-containing film to obtain SiO2 coating.

[0010] Compared with the prior art, the present application has the following advantages: first, a layer of energy-containing film is deposited on the surface of C / C composite material reinforced by carbon fiber and carbon matrix, which contains components that can release heat when the combustion reaction is initiated, promoting the pyrolysis and reaction of SiO2 precursor, thereby rapidly forming SiO2 coating and realizing high-efficiency deposition of SiO2 coating. Because ZrO2 nanoparticles are used as energy storage components, they absorb excess heat energy and gradually release it, avoiding heat damage to the substrate. Because the wettability of the substrate is improved, the energy-containing film has high density, and the density of the obtained SiO2 coating is also guaranteed. The entire coating preparation process takes no more than 9 hours, which is shorter than the process cycle of the prior art.

[0011] In one possible implementation, the substrate pretreatment in step S1 is to clean the C / C composite material with an ethanol-acetone mixed solution, then spray 3-aminopropyl triethoxysilane solution and dry.

[0012] In one possible implementation, the ethanol-acetone mixed solution is obtained by mixing ethanol and acetone in a volume ratio of 1:1; the mass concentration of the 3-aminopropyl triethoxysilane solution is 0.5-1.5%, and the solvent is ethanol.

[0013] In one possible implementation, the exothermic component of the energy-containing film is Al-Fe2O3.

[0014] In a possible implementation, the exothermic component of the energetic film is Al-Fe2O3, and the energetic film is prepared by the following method: Fe2O3 nanoparticles and graphene oxide are dispersed in an isopropyl alcohol solution, and then Al nanoparticles and polyvinylpyrrolidone are added, and mixed to obtain an Al-Fe2O3-GO suspension; the product obtained in step S1 is alternately immersed in the Al-Fe2O3-GO suspension and deionized water, and then dried in an inert atmosphere, and then densified by electrophoretic deposition to obtain the energetic film.

[0015] In a possible implementation, the molar ratio of Al to Fe2O3 in the exothermic component of the energetic film is 2:1, and the particle size of the Al nanoparticles is 50-200 nm; the amount of graphene oxide added accounts for 10-15 wt% of the total mass of the energetic film.

[0016] In a possible implementation, the concentration of the Al-Fe2O3-GO suspension is 1-5 mg / mL.

[0017] In a possible implementation, the thickness of the obtained energetic film is 10-20 μm, and the porosity is <2%.

[0018] In a possible implementation, the SiO2 precursor is a mixture obtained by mixing tetraethyl orthosilicate and ethanol at a ratio of 1:4.

[0019] In a possible implementation, the particle size of the ZrO2 nanoparticles is 100-200 nm, and the porosity of the coating is <5%.

[0020] The present application has the following advantages:

[0021] (1) In the preparation method of the present application, the heat released by the exothermic component of the energetic film promotes the pyrolysis and reaction of the SiO2 precursor, thereby rapidly forming a SiO2 coating and realizing efficient deposition of SiO2 in the coating. The energy storage effect of the ZrO2 nanoparticles absorbs the excess heat energy of the reaction and gradually releases it, avoiding thermal damage to the substrate. Due to the improved wettability of the substrate, the deposited energetic film has high density, and the density of the obtained SiO2 coating is also guaranteed. The problem of mutual restriction among density, process efficiency, and thermal damage to the substrate in the prior art is solved.

[0022] (2) Innovative design of energetic film

[0023] Construction of ternary composite system: Al-Fe2O3-graphene oxide ternary composite energetic film is used, in which graphene oxide is used as an interfacial reinforcing agent. The released CO2 gas initiates a chain acceleration of the aluminothermic reaction of Al and Fe2O3, and the reaction temperature can reach 2000℃, which improves the heat conduction efficiency of the reaction and makes the preparation method economical and efficient.

[0024] (3) Interfacial interlocking structure

[0025] The two-dimensional network of graphene oxide mechanically interlocks with Al, Fe2O3 particles, and the shear bonding force is improved to 40 MPa, so that the film bonding force is strong.

[0026] (4) Synchronous pyrolysis-deposition process

[0027] The high temperature released by the energetic film directly activates the pyrolysis of the TEOS precursor, generates amorphous SiO2 and fills the pores in situ, so that the coating density reaches 98.5%; the coating thickness can be controlled by the number of energetic film layers, and the single deposition thickness reaches 2-5 μm. The process of pyrolysis to generate SiO2 is completed instantaneously, realizing rapid and efficient preparation of SiO2 coating.

[0028] (5) Thermal shock buffering technology

[0029] The ZrO2 nanoparticle energy storage component is introduced to buffer the thermal shock through phase change heat absorption, and the temperature gradient of the substrate is reduced to <50℃ / μm, avoiding the substrate crack problem of traditional laser cladding. BRIEF DESCRIPTION OF DRAWINGS

[0030] Figure 1 The water contact angle picture of the C / C composite material pretreated in the embodiment 1 of the present application;

[0031] Figure 2 The scanning electron microscope picture of ZrO2 nanoparticles;

[0032] Figure 3 The scanning electron microscope picture of the C / C composite material pretreated in the embodiment 1 of the present application;

[0033] Figure 4 The scanning electron microscope picture of the SiO2 coating on the surface of the C / C composite material prepared in the embodiment 1 of the present application. DETAILED DESCRIPTION

[0034] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific embodiments of the present application are described in detail below. It should be noted that the following embodiments are only used to illustrate the implementation method and typical parameters of the present application, and do not limit the parameter range described in the present application, and the reasonable changes derived therefrom are still within the protection scope of the claims of the present application.

[0035] It is to be understood that the endpoints of the ranges specified in this disclosure are not to be understood as being limited to the exact values recited as the endpoints of those ranges. It is to be understood that the endpoints of each of the ranges are provided as approximations to the endpoints of these ranges in this disclosure. Unless otherwise stated, each numerical value and range should be interpreted as a preference for another numerical value or range in the stated ranges. This is also to be understood to apply to any numerical value or range that is expressed as an approximation of a numerical value or range.

[0036] Unless otherwise defined, all terms, symbols and other scientific terminology used herein are to be interpreted in accordance with their ordinary meaning within the technical field, unless a differently specific meaning is given herein. In some cases, terms that are commonly understood by those skilled in the art are defined herein for the sake of clarity or convenience, and such definitions should not be interpreted as indicating a significant difference from the common understanding of those terms in the art. The technical methods described or referenced herein are generally well understood by those skilled in the art and are employed by conventional methods. Unless otherwise stated, the use of commercially available kits and reagents, instruments is carried out according to the protocols and parameters given by the manufacturer.

[0037] The present application provides a method for rapidly generating SiO2 coating by energy-containing thin film reaction coupled with gradient thermal field regulation. The specific steps are as follows:

[0038] 1. Pretreatment of the substrate

[0039] The C / C composite material is immersed in an ethanol-acetone mixed solution (volume ratio of 1:1) and ultrasonically cleaned at a frequency of 40 kHz for 20-30 minutes to remove adsorbed impurities in the pores. A 3-aminopropyl triethoxysilane solution (mass concentration of 0.5-1.5%, solvent is ethanol) is sprayed and dried to form a chemical bonding interface layer, improving the surface wettability (contact angle ≤90°).

[0040] 2. Deposition of Al-Fe2O3-graphene oxide ternary composite energy-containing thin film by alternating immersion method

[0041] (1) Material ratio optimization

[0042] A ternary composite system is formed by Al powder, Fe2O3 nanoparticles and graphene oxide (GO), with a molar ratio of Al:Fe2O3=2:1 and a mass fraction of graphene oxide in the three components of 10-15wt%. Graphene oxide acts as an interface reinforcing agent, and its surface oxygen-containing functional groups (-COOH, -OH) can provide chemical bonding sites, improving the film density and energy transfer efficiency.

[0043] (2) Deposition process steps

[0044] Step one: dispersion of binary composite

[0045] Fe2O3 and graphene oxide were added into isopropyl alcohol solution with a molar ratio of 1:2, and ultrasonic dispersion was performed for 0.5-3 hours to form a uniform suspension (concentration 1-5 mg / mL).

[0046] Step two: aluminum particle loading

[0047] Al nanopowder (particle size 50-200 nm) and dispersant (such as polyvinylpyrrolidone) were added into isopropyl alcohol and ultrasonic treatment was performed for 30 minutes. After mixing with the suspension of step one, ultrasonic treatment was continued for 1 hour to obtain an Al-Fe2O3-GO suspension.

[0048] Step three: alternate immersion deposition

[0049] The pretreated C / C composite material substrate was alternately immersed in the Al-Fe2O3-GO suspension and deionized water, and each cycle of immersion time was 5-10 minutes, and the cycle number was 10-30 times, and finally a composite film with a thickness of 10-20 μm was formed.

[0050] (3) Post-treatment and performance improvement

[0051] The composite film obtained in (2) was vacuum dried at 80-120°C under nitrogen protection to eliminate interface pores; and through electrophoretic deposition (voltage 20-50 V, time 2-5 minutes), further densification was performed to obtain an energetic film, and the porosity of the obtained energetic film was reduced to <2%.

[0052] It should be noted that any existing energetic film in the technical solution of the present application can meet the use requirements in the concept of the present application, and the application mechanism of the energetic film is in the heat release component. The Al-Fe2O3-graphene oxide ternary composite energetic film mentioned above is a preferred heat release component example given by the present application. Of course, according to the concept of the present application, other components can also be selected, such as the newly developed heat release component CL-20 of the energetic film in recent years.

[0053] 3. SiO2 precursor coating

[0054] Tetraethyl orthosilicate (TEOS) and ethanol were mixed at a ratio of 1:4, and the mixture was coated on the surface of the energetic film by a hot dipping method.

[0055] 4. Reaction-induced coating formation

[0056] ZrO2 nanoparticles are coated on SiO2 precursor, the ZrO2 nanoparticles are ball milled for 12 hours, spray-dried granulation (particle size 100-200 nm), and plasma spraying is carried out according to the following parameters: plasma power: 40 kW, Ar gas flow rate 50 L / min, H2 flow rate 10 L / min; spraying distance: 80-100 mm, powder feeding rate 20 g / min; a composite coating in which ZrO2 nanoparticles are uniformly embedded in a SiO2 matrix is formed, and the porosity of the coating is <5%.

[0057] Then, the energetic film is ignited by laser or electric spark to release a high temperature (up to 1800-2000 DEG C) to promote the pyrolysis of TEOS to form amorphous SiO2; at the same time, ZrO2 nanoparticles are introduced as an energy storage component to absorb excess heat energy and gradually release it, thereby avoiding thermal damage to the matrix.

[0058] In order to more clearly illustrate the technical solutions and advantages of the present application, the present application will be described in detail below through several examples.

[0059] The wettability of the surface of the C / C composite material is measured by a contact angle tester (JY-82B Kruss DSA), the test sample is placed on a sample table, ultrapure water is used as the liquid drop for testing, 5 μL of ultrapure water is dropped onto the sample surface during measurement, and the liquid drop image is quickly collected to measure the contact angle.

[0060] Example 1

[0061] 1. Pretreatment of the matrix

[0062] The C / C composite material is immersed in an ethanol-acetone mixed solution (volume ratio 1:1) and ultrasonically cleaned at a frequency of 40 kHz for 25 minutes to remove the adsorbed impurities in the pores, and the surface structure of the pretreated C / C composite material is as shown in FIG. 1. A 3-aminopropyl triethoxysilane solution with a mass concentration of 1% is sprayed, and the surface is dried at 80 DEG C to form a chemical bonding interface layer, at which time the surface contact angle is measured to be ≤90 DEG C, as shown in FIG. 2, which is 36 DEG C, indicating that the surface wettability is good. Figure 3 Figure 1

[0063] 2. Deposition of Al-Fe2O3-graphene oxide ternary composite energetic film by alternating immersion method

[0064] (1) Material ratio optimization: a ternary composite system composed of Al powder, Fe2O3 nanoparticles and graphene oxide (GO) is used, the molar ratio of Al:Fe2O3 is 2:1, and the mass ratio of graphene oxide in the three is 10wt%.

[0065] (2) Deposition process steps

[0066] ​​Binary composite dispersion: Fe2O3 and graphene oxide were added into isopropanol solution at a molar ratio of 1:2, ultrasonic dispersion for 2 hours to form a uniform suspension with a concentration of 3 mg / mL.

[0067] Aluminum particle loading: Al nanopowder with a particle size of 100 nm and polyvinylpyrrolidone were added to isopropanol and ultrasonically treated for 30 minutes. After mixing with the above suspension, ultrasonic treatment was continued for 1 hour to obtain an Al-Fe2O3-GO suspension.

[0068] Alternating immersion deposition: The pretreated C / C composite substrate was alternately immersed in the Al-Fe2O3-GO suspension and deionized water, with each cycle of immersion time being 8 minutes and the number of cycles being 20 times, to finally form a composite film with a thickness of about 15 μm.

[0069] (3) Post-treatment and performance improvement: The composite film was vacuum dried at 100°C under nitrogen protection to eliminate interfacial pores; further densification was achieved by electrophoretic deposition (voltage 30 V, time 3 minutes) to obtain an energetic film, which was detected to have a porosity of <2%.

[0070] 3. SiO2 precursor coating

[0071] Tetraethyl orthosilicate (TEOS) was mixed with ethanol at a ratio of 1:4 and coated on the surface of the energetic film by hot dipping.

[0072] 4. Reaction-induced coating formation

[0073] ZrO2 nanoparticles were coated on the SiO2 precursor by plasma spraying technology, as shown in Figure 2 ; then the energetic film was ignited by laser to release a transient high temperature of up to 2000°C, which promoted the pyrolysis of TEOS to form amorphous SiO2; the introduced ZrO2 nanoparticles acted as an energy storage component, absorbing excess heat energy and gradually releasing it, effectively avoiding thermal damage to the substrate, and a SiO2 coating on the surface of the C / C composite material was obtained, as shown in Figure 4 ; the obtained SiO2 coating had good denseness.

[0074] Example 2

[0075] 1. Substrate pretreatment

[0076] The C / C composite material was immersed in an ethanol-ketone mixed solution (volume ratio 1:1) and ultrasonically cleaned at a frequency of 40 kHz for 25 minutes to remove adsorbed impurities in the pores. A 3-aminopropyltriethoxysilane solution with a mass concentration of 1% was sprayed, and the surface was dried at 80°C to form a chemical bonding interface layer. At this time, the surface contact angle was measured to be ≤90°, and the surface wettability was good.

[0077] 2. Deposition of Al-Fe2O3-graphene oxide ternary composite energetic film by alternating immersion method

[0078] (1) Material ratio optimization: A ternary composite system composed of Al powder, Fe2O3 nanoparticles and graphene oxide (GO) is adopted, with a molar ratio of Al: Fe2O3 = 2: 1, and the mass fraction of graphene oxide in the three is 12wt%.

[0079] (2) Deposition process steps

[0080] Binary compound dispersion: Fe2O3 and graphene oxide are added to isopropanol solution in a molar ratio of 1:2, ultrasonic dispersion for 2 hours, forming a uniform suspension with a concentration of 3mg / mL.

[0081] Aluminum particle loading: Al nanopowder with a particle size of 100nm and polyvinylpyrrolidone are added to isopropanol and ultrasonic treated for 30 minutes, mixed with the above suspension and continue to ultrasonic for 1 hour, get Al-Fe2O3-GO suspension.

[0082] Alternating immersion deposition: The pretreated C / C composite material substrate is alternately immersed in Al-Fe2O3-GO suspension and deionized water, with a cycle immersion time of 8 minutes, and a cycle number of 20 times, finally forming a composite film with a thickness of about 15μm.

[0083] (3) Post-processing and performance improvement: The composite film is vacuum dried at 100℃ under nitrogen protection to eliminate interface pores; further densification is carried out by electrophoretic deposition (voltage 30V, time 3 minutes) to obtain an energetic film, and the porosity of the obtained energetic film is reduced to <2%.

[0084] 3, SiO2 precursor coating

[0085] Tetraethyl orthosilicate (TEOS) and ethanol are mixed in a ratio of 1:4 and coated on the surface of the energetic film by hot dipping method.

[0086] 4, Reaction-induced coating formation

[0087] ZrO2 nanoparticles are coated on the SiO2 precursor by plasma spraying technology, and then the energetic film is ignited by laser to release a transient high temperature of up to 2000℃, which promotes the pyrolysis of TEOS to form amorphous SiO2; the introduced ZrO2 nanoparticles act as energy storage components, absorbing excess heat energy and gradually releasing it, effectively avoiding thermal damage to the substrate, and obtaining a SiO2 coating on the surface of the C / C composite material.

[0088] Example 3

[0089] 1, Substrate pretreatment

[0090] The C / C composite material is immersed in an ethanol-acetone mixed solution (volume ratio 1:1) and ultrasonically cleaned for 25 minutes at a frequency of 40 kHz to remove the adsorbed impurities in the pores. A 3-aminopropyl triethoxysilane solution with a mass concentration of 1% is sprayed, and a chemical bonding interface layer is formed after drying at 80°C. At this time, the surface contact angle is measured to be ≤90°, and the surface wettability is good.

[0091] 2. Al-Fe2O3-graphene oxide ternary composite energetic film deposited by alternate immersion method

[0092] (1) Material ratio optimization: A ternary composite system composed of Al powder, Fe2O3 nanoparticles and graphene oxide (GO) is adopted, with a molar ratio of Al:Fe2O3=2:1 and a mass ratio of graphene oxide in the three of 15wt%.

[0093] (2) Deposition process steps

[0094] Binary composite dispersion: Fe2O3 and graphene oxide are added to isopropanol solution at a molar ratio of 1:2, ultrasonically dispersed for 2 hours, and a uniform suspension with a concentration of 3mg / mL is formed.

[0095] Aluminum particle loading: Al nanopowder with a particle size of 100nm and polyvinylpyrrolidone are added to isopropanol and ultrasonically treated for 30 minutes. After mixing with the above suspension and continuing ultrasonic treatment for 1 hour, an Al-Fe2O3-GO suspension is obtained.

[0096] Alternate immersion deposition: The pretreated C / C composite material substrate is alternately immersed in the Al-Fe2O3-GO suspension and deionized water, with each cycle of immersion time being 8 minutes and the cycle number being 20 times, to finally form a composite film with a thickness of about 15μm.

[0097] (3) Post-treatment and performance improvement: The composite film is vacuum dried at 100°C under nitrogen protection to eliminate the interface pores; an energetic film is further densified by electrophoretic deposition (voltage 30V, time 3 minutes), and the porosity of the obtained energetic film is reduced to <2% after detection.

[0098] 3. SiO2 precursor coating

[0099] Tetraethyl orthosilicate (TEOS) is mixed with ethanol at a ratio of 1:4 and coated on the surface of the energetic film by hot dipping.

[0100] 4. Reaction-induced coating formation

[0101] ZrO2 nanoparticles are coated on SiO2 precursor by plasma spraying technology, then laser ignites energetic film, releases transient high temperature up to 2000 DEG C, promotes TEOS pyrolysis to generate amorphous SiO2; ZrO2 nanoparticles are introduced as energy storage component, absorb excess heat energy and gradually release, effectively avoids thermal damage of the matrix, and obtains SiO2 coating on the surface of C / C composite material.

[0102] The SiO2 coating on the surface of C / C composite material obtained by the above three embodiments has a density of more than 98.5%, and the matrix of the composite material has little damage, which shows that the method for rapidly preparing SiO2 coating on the surface of C / C composite material is effective.

[0103] The above is only a specific embodiment of the present application, but the protection scope of the present application is not limited to this, any person skilled in the art can easily think of changes or replacements within the technical range disclosed by the present application, which should be covered in the protection scope of the present application. Therefore, the protection scope of the present application should be subject to the protection scope of the claims.

Claims

1. A method for rapidly preparing a SiO2 coating on a C / C composite material surface, characterized in that, The method comprises the following steps: Step S1, pretreating the matrix of the C / C composite material to improve the surface wettability; Step S2, depositing an energetic film on the surface of the product obtained in step S1; Step S3, coating a SiO2 precursor on the surface of the product obtained in step S2, coating ZrO2 nanoparticles on the SiO2 precursor, igniting the energetic film, and obtaining a SiO2 coating.

2. The method for rapidly preparing a SiO2 coating on the surface of a C / C composite material according to claim 1, characterized in that, The matrix pretreatment in step S1 is to clean the C / C composite material with an ethanol-acetone mixed solution, then spray 3-aminopropyl triethoxysilane solution and dry.

3. The method for rapidly preparing a SiO2 coating on the surface of a C / C composite material according to claim 2, characterized in that, The ethanol-acetone mixed solution is obtained by mixing ethanol and acetone at a volume ratio of 1:1; the mass concentration of the 3-aminopropyl triethoxysilane solution is 0.5-1.5%, and the solvent is ethanol.

4. The method for rapidly preparing a SiO2 coating on a C / C composite material surface according to claim 1, characterized in that, The exothermic component of the energetic film is Al-Fe2O3.

5. The method for rapidly preparing a SiO2 coating on the surface of a C / C composite material according to claim 4, characterized in that, The exothermic component of the energetic film is Al-Fe2O3, and the energetic film is prepared by the following method: dispersing Fe2O3 nanoparticles and graphene oxide in an isopropanol solution, then adding Al nanopowder and polyvinylpyrrolidone, mixing to obtain an Al-Fe2O3-GO suspension; alternately immersing the product obtained in step S1 in the Al-Fe2O3-GO suspension and deionized water, then drying in an inert atmosphere, and then densifying the energetic film by electrophoretic deposition.

6. The method for rapidly preparing a SiO2 coating on the surface of a C / C composite material according to claim 5, characterized in that, The molar ratio of Al to Fe2O3 in the exothermic component of the energetic film is 2:1, the particle size of the Al nanopowder is 50-200 nm, and the graphene oxide accounts for 10-15 wt% of the total mass of the energetic film.

7. The method for rapidly preparing a SiO2 coating on a C / C composite material surface according to claim 5, characterized in that, The concentration of the Al-Fe2O3-GO suspension is 1-5 mg / mL.

8. The method for rapidly preparing a SiO2 coating on a C / C composite material surface according to claim 5, characterized in that, The thickness of the obtained energetic film is 10-20 μm, and the porosity is <2%.

9. The method for rapidly preparing a SiO2 coating on a C / C composite material surface according to claim 1, characterized in that, The SiO2 precursor is a mixture of tetraethyl orthosilicate and ethanol at a ratio of 1:

4.

10. The method for rapidly preparing a SiO2 coating on a C / C composite material surface according to claim 1, characterized in that, The particle size of the ZrO2 nanoparticles is 100-200 nm, and the coating porosity is <5%.

Citation Information

Patent Citations

  • A method for preparing a B2O3@SiO2 core-shell-SiC coating on the surface of a C / C composite material and the composite coating

    CN114644531B

  • C / C composite material crucible capable of grinding SiC coating and preparation method

    CN118812275A

  • Novel ablation-resistant gradient composite coating of C / C composite material and preparation method

    CN118878352A

  • Preparation method of anti-oxidation coating on surface of C / C composite material, anti-oxidation C / C composite material and application of anti-oxidation C / C composite material

    CN118955182A

  • Preparing method of SiC-ZrC gradient modified carbon / carbon composite material

    CN106045550A